Legislation of the Republic of Belarus and the Russian Federation on pardon: on the issue of improving - Grishko, Alexander Y. (Journal of the Belarusian State University. Law, 2019)
The article provides a comparative analysis of legislation of the Republic of Belarus and the Russian Federation, regulating the use of pardons, along with common specifics of laws and normative legal acts of the countries in this area. The author offers ways of improvement of legal regulation of this institute. The proposal argued for relevant scientific points of view.